2017
DOI: 10.20546/ijcrbp.2017.411.012
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Potential Orphan Plants in Health Management and Climate Change Mitigation from Bahraich (Uttar Pradesh), India

Abstract: Crop species which are adapted to hot and dry climates will become increasingly important as the world worms. The Krikhouse Trust* supporting research and education in the biological Sciences is devoted for agricultural crop improvement for the relief of poverty, with a focus on legumes. The trust has supported research on legumes because of their importance in providing high quality protein in the diets of resource-poor farmers. Among these crops are many stress tolerant legume species found in India and Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Globally, underexploited legumes are known as nutritious resources and can be intended to improve health [ 4 ] and minimize disease risks [ 5 ]. They have a specific profile with high nutrient and protein content alternatives to maintain farmers’ livelihoods and soil protection [ 6 ]. In comparison, underexploited legumes are a less utilized potential source to improve protein and micronutrient content in comparison to cereals which provided ample calories but insufficient micronutrients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, underexploited legumes are known as nutritious resources and can be intended to improve health [ 4 ] and minimize disease risks [ 5 ]. They have a specific profile with high nutrient and protein content alternatives to maintain farmers’ livelihoods and soil protection [ 6 ]. In comparison, underexploited legumes are a less utilized potential source to improve protein and micronutrient content in comparison to cereals which provided ample calories but insufficient micronutrients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These plants are traditionally used for many health disorders, e.g., headache, fever, diabetes, diarrhea, parasitic infections, peptic ulcer and rheumatism [4] . Biologically, it was reported that some Ceiba species possess wide range of useful anti-inflammatory, hepato-protective, cytotoxic, antioxidant and hypoglycemic with high safety margins [5,6] . Free radicals are a kind of high-energy unstable reactive substances that contain odd numbers of electrons, which can penetrate human cells and tissues and cause abnormal cell growth [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Horse gram [Macrotyloma uniflorum (Lam.) Verdc] is an orphan and/or underutilized crop largely grown locally by communities as cultural heritage in special niches in developing countries (Chahota et al 2013;Uma et al 2013;Bhartiya et al 2015;Cullis and Kunert 2017;Ellis 2016;Mall 2017;Fuller and Murphy 2018). Although this orphan legume serves as an important component of diets of resource-poor masses to provide balanced nutrition, feed for animals in drought-prone regions along with their potential health and environmental benefits, it has been typically overlooked in terms of resources for their promotion as well as not being traded internationally due to the limited economic importance in the global market (Bhartiya et al 2015;Cullis and Kunert 2017).…”
Section: Introductionmentioning
confidence: 99%